Un couple, deux carrières: quelques considérations - Desjardins, Edwidge; Langelier, Régis (Canadian Journal of Counselling and Psychotherapy, 2012)
More and more women are pursuing a career and the dual career couple is commonplace. This family life style offers new sources of satisfaction to individuals, but also offers new problems to the couple. A primary difficulty is balancing both career and relationship demands. Two important issues related to this difficulty are: the problems encountered mostly by women and the importance of male support for their solutions, and the issue of time pressure and time management.